2022
DOI: 10.3390/su14137614
|View full text |Cite
|
Sign up to set email alerts
|

Does the Adoption of Mobile Internet Technology Promote Wheat Productivity? Evidence from Rural Farmers

Abstract: The adoption of mobile Internet technology (MIT) in organizational systems is rapidly increasing. MIT has developed agricultural structures and dramatically altered farming activities to improve agricultural systems. MIT is considered one of the most essential technologies because of its huge impact on agriculture, economy, and our daily lives. In this study, we utilized sample data from 460 wheat growers in the Khyber Pakhtunkhwa (KP) province of Pakistan to analyze the adoption of MIT and its impact on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 80 publications
(104 reference statements)
0
8
1
Order By: Relevance
“…The adoption of mobile internet has no significant effect. This result is different from these previous studies [22,54]. However, the adoption of mobile internet could classify into various scope of activities such as the marketing activities (price monitoring or selling activity) and the production activities (digital farming, related with the improvement of production).…”
Section: The Impact Of Internet On Productivitycontrasting
confidence: 75%
See 3 more Smart Citations
“…The adoption of mobile internet has no significant effect. This result is different from these previous studies [22,54]. However, the adoption of mobile internet could classify into various scope of activities such as the marketing activities (price monitoring or selling activity) and the production activities (digital farming, related with the improvement of production).…”
Section: The Impact Of Internet On Productivitycontrasting
confidence: 75%
“…The promotion of internet of thing (IoT) could increase the productivity of small farmers in Mexico [54]. Khan et al [22] revealed that the impact of mobile internet technology on wheat productivity is positive and significant. Therefore, the adoption of mobile internet has a positive effect on the productivity.…”
Section: The Effect Of Internet On Palm Oil Productivitymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the above-mentioned hypotheses, we would also like to discover how the smartphone decision affects the financial performance of agricultural households. Khan et al (2022) showed that the adoption of mobile Internet technology boosted agricultural output, which in turn increased the revenue of agricultural producers. Even though mobile phones can serve as a catalyst for increased farm production and rural incomes, the quality, timeliness, and credibility of this information must be conveyed to farmers to fulfill their requirements and expectations (Mittal & Tripathi, 2009).…”
Section: Mobile Phone Adoption and Financial Performancementioning
confidence: 99%